Analysis of the reproductive viability of Varroa destructor (Mesostigmata: Varroidae) rearing under laboratory conditions - Jesús Humberto Reyna-Fuentes; Cecilia Carmela Zapata Campos; Fabian Eliseo Olazarán Santibanez; José Octavio Merino Charrez; Daniel López Aguirre (Persian Journal of Acarology, 2025)
The Varroa destructor Anderson & Trueman, 2000 (Mesostigmata: Varroidae) is one of the most detrimental pests for the physiology and productivity of Apis mellifera (Hymenoptera: Apidae) in the international context. To study its reproductive behavior, different rearing protocols have been developed over the years under semi-natural or laboratory conditions. However, V. destructor has low survival capacity and does not reproduce successfully outside its natural environment and hosts. As a result, the availability of these mites for experimental purposes is limited. This research aimed to evaluate the reproductive viability of V. destructor mites under laboratory conditions, using gelatin capsules with single and double infestation by bee pupae (5th instar). All data were analyzed using generalized linear mixed models implemented in Proc GLIMMIX using the binary distribution function with the default logit link function. For both treatments (capsule with 1 and 2 mother mites), a significant effect was shown for the mean number of broods (p < 0.0001). The reproduction of mother mites in both treatments showed significant effects (p < 0.05). Males were observed more frequently in capsules infested with two V. destructor mother mites (p = 0.001). For the case of pupae mortality with two mites a significant value of p < 0.0007 was reported, as well as with the presence of one mite p < 0.0040, however, no significant differences between them were demonstrated. In conclusion, these results showed that in vitro V. destructor rearing using gelatin capsules is a useful tool for future research work. However, it is intended to continue modifying this protocol to find higher values of survival and reproductive success of mites, to analyze the biological parameters of V. destructor in studies involving a high number of adult mites, several generations, and reproductive cycles.